2016
DOI: 10.1167/iovs.16-19568
|View full text |Cite
|
Sign up to set email alerts
|

Macular Inner Retinal Layer Thickening and Outer Retinal Layer Damage Correlate With Visual Acuity During Remission in Behcet's Disease

Abstract: Behcet's disease patients in remission had significant changes in the inner and outer retinal structures, associated with worse VA. Thickness and integrity of the intraretinal layers by SD-OCT and segmentation might be useful predictors for the degree of VA damage in BD remission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 46 publications
0
27
0
4
Order By: Relevance
“…14,15 Disorders of the outer retina and progressive damage to photoreceptors have also been demonstrated in BD. [16][17][18] These findings indicate that the outer retinal disruption and choroidal disorders in BD may be related to changes in the inner retinal vasculature.…”
mentioning
confidence: 78%
See 2 more Smart Citations
“…14,15 Disorders of the outer retina and progressive damage to photoreceptors have also been demonstrated in BD. [16][17][18] These findings indicate that the outer retinal disruption and choroidal disorders in BD may be related to changes in the inner retinal vasculature.…”
mentioning
confidence: 78%
“…Informed consent was obtained from all patients and subjects before imaging. The inclusion criteria for the BD groups were fulfillment of the diagnostic criteria developed by the International Study Group for Behçet's Disease, 24 BD in remission, 18 and evidence of posterior segment involvement. 25,26 Exclusion criteria for eyes with BD were anterior uveitis only, a spherical equivalent refractive error greater than 66.0 diopters, significant cataract or vitreous opacity, diabetic retinopathy, age-related macular degeneration, glaucoma, other marked complications, or a history of intraocular surgery within the previous year.…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…2C) as already described in our previously published articles. 21,22 Manual inspection and a few corrections were still required, especially in low-quality images. In the current study, the retina was divided into retinal nerve fiber layer (RNFL), ganglion cell layer and inner plexiform layer (GCIP), inner nuclear layer (INL), outer plexiform layer (OPL), Henle fiber layer and outer nuclear layer (HFLþONL), myoid and ellipsoid zone (MEZ), outer segment of the photoreceptor cell (OS), and interdigitation zone and retinal pigment epithelium (IZþRPE).…”
Section: Sd-oct Procedures and Data Collectionmentioning
confidence: 99%
“…Proposed mechanisms for GCL thickening in nonexudative AMD include: compensatory proliferation and migration of inter-neuronal cells, 14,40 and reactions to the inflammatory processes in AMD. 41,42 Increased GCL thickness may reflect glial cell hypertrophy and/or neuron migration in the inner retina, events common in other photoreceptor degenerations, such as retinitis pigmentosa. 40 This is supported by recent work of Jones et al 8 who demonstrated translocation of amacrine cells and changes in Müller cell metabolomics in postmortem advanced AMD eyes.…”
Section: Proposed Mechanisms For Gcl Changesmentioning
confidence: 99%